1990
DOI: 10.1159/000457623
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Beta-Agonist in Ventilated, Very-Low-Birth-Weight Babies: A Longitudinal Evaluation

Abstract: To determine if there is a specific postnatal (PNA) or postconceptional age (PCA) at which ventilated preterm infants respond to β-agonists, we evaluated 15 infants with a mean gestational age of 26.5 ± 1.5 weeks and mean birth weight of 0.89 ± 0.23 kg who required mechanical ventilation at 10 days of age. Weekly pulmonary function testing (PFT) was performed before and 1 h after administration of albuterol. Taking the group as a whole, as well as individual babies, regression analysis showed no relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…A Cochrane Database Systemic Review found that this was the only study adequate to assess bronchodilator effect on the prevention of BPD, and there were no eligible studies to determine the effect of bronchodilation on the treatment of BPD [56]. Because of the potential side effects, variability of administration, and paucity of long-term benefits, one must reserve bronchodilator therapy for infants with evidence of bronchospasm (ie, prolonged expiratory phase, increased work of breathing) and clinical improvement after therapy [57][58][59].…”
Section: Bronchodilatorsmentioning
confidence: 99%
“…A Cochrane Database Systemic Review found that this was the only study adequate to assess bronchodilator effect on the prevention of BPD, and there were no eligible studies to determine the effect of bronchodilation on the treatment of BPD [56]. Because of the potential side effects, variability of administration, and paucity of long-term benefits, one must reserve bronchodilator therapy for infants with evidence of bronchospasm (ie, prolonged expiratory phase, increased work of breathing) and clinical improvement after therapy [57][58][59].…”
Section: Bronchodilatorsmentioning
confidence: 99%
“…Airway smooth muscle is present in the preterm airways and contains neural elements responsive to cholinergic and other constrictive stimuli [ 3 ], which may precipitate airway narrowing, worsen respiratory mechanics, and lead to hypoxemia. The preterm airways also contain β2-adrenergic receptors (β2-AR) capable of agonist-stimulated bronchodilation [ 4 ]. Preterm infants at high risk for chronic lung disease show evidence of hypertrophy of airway muscle as early as 10 days of age [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is not uncommon for NICU clinicians and respiratory therapists to use inhaled β2-AR agonists, such as albuterol, to potentially relieve bronchoconstriction and wheezing, decrease airway resistance, and improve oxygenation in preterm infants with evolving and established chronic lung disease [ 6 – 10 ]. While systematic reviews have not shown convincing data of their efficacy in the prevention of chronic lung disease or other long-term morbidities associated with prematurity [ 11 , 12 ], many preterm infants do show improvements in pulmonary function testing following inhaled β2-AR agonist therapy [ 4 , 13 16 ]. Of note, some infants may never be responders in the NICU [ 4 , 16 ] or have the potential to develop tolerance and become non-responders over time [ 13 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the perinatal period, infants with evolving BPD are frequently treated for airway hyperreactivity ( Mhanna et al, 2009 ; Slaughter et al, 2015 ), but first-line therapies such as β 2-adrenergic agonists lack consistent bronchodilator efficacy ( Motoyama et al, 1987 ; Kovacs et al, 1990 ; Denjean et al, 1992 ) and have not been shown to prevent BPD nor facilitate weaning of respiratory support ( Denjean et al, 1998 ). Of note, older children with BPD also have airway hyperreactivity that is distinct from allergic T-helper-2-high asthma ( Halvorsen et al, 2005 ; Siltanen et al, 2011 ; Filippone et al, 2013 ) and may have minimal or even a paradoxical response to traditional asthma medications ( Yuksel and Greenough, 1993 ; De Boeck et al, 1998 ; Baraldi et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%